Anti-crack fully-recycled aggregate road water-stable layer material and preparation method thereof
By using industrial solid waste such as fly ash and construction waste to prepare crack-resistant, fully recycled aggregate water-stabilized layer materials, the problems of insufficient performance of water-stabilized layer materials and waste disposal have been solved. This has enabled the preparation of high-strength, low-carbon, and environmentally friendly water-stabilized layer materials that meet the requirements of highway engineering.
Patent Information
- Application Number
- CN202410665789.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-11-28
AI Technical Summary
The overall performance of existing water-stabilized layer materials needs to be further improved, especially their mechanical properties, durability, and stability. In addition, the processing pressure of construction waste and tailings sand and gravel is relatively high, and the resource utilization rate is low.
Using industrial solid waste and construction waste such as fly ash, slag powder, silica fume or red mud as the main raw materials, combined with water-reducing agents, retarders and air-entraining agents, crack-resistant fully recycled aggregate road water-stabilized layer materials are prepared. Through gradation and uniform mixing treatment, the process meets the requirements of low cement consumption and low consumption of natural crushed stone.
This invention achieves a water-stabilized layer material with high strength, crack resistance, and excellent impermeability, solving the problem of construction waste disposal, reducing production costs and carbon emissions, meeting the requirements of green development, and improving the overall performance of the material.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of road construction, and particularly relates to an anti-cracking full-regeneration aggregate road water-stable layer material and a preparation method thereof. BACKGROUND
[0002] With the continuous acceleration of industrialization and urbanization, people's requirements for the comprehensive performance of roads are also constantly improving. Among them, the water-stable layer, as the main bearing layer of the road surface, is an important part of the road surface. The addition amount, particle size and processing method of the recycled aggregate can significantly affect the physical and mechanical properties of the cement stabilized macadam. How to improve the comprehensive performance of the water-stable layer has become one of the research hotspots of the staff in the building material field. However, the comprehensive performance of the water-stable layer material in the prior art still needs to be further improved, so as to expand the actual use range of the recycled aggregate water-stable layer material.
[0003] The Chinese invention patent with the patent publication number CN113698164A discloses an anti-cracking road water-stable layer material. In the patent, slag powder, cement, fly ash and other materials are added to the building gypsum to interact with the additives, modify the building gypsum, and focus on solving the problems of easy cracking and settlement of the water-stable material in the prior art. However, the mechanical properties, durability and stability of the water-stable material still need to be further improved.
[0004] At the same time, with the rapid development of infrastructure construction, the amount of construction waste, road demolition waste or tailings sandstone is increasing, which brings serious pressure to the environment. It is an urgent task to treat construction waste, road demolition waste or tailings sandstone, and it is of great significance to fully utilize construction waste, road demolition waste or tailings sandstone resources and promote the transformation of the construction industry to a circular economy. Therefore, finding a kind of full-regeneration aggregate road water-stable layer material prepared by using recycled aggregate in large quantities and its preparation method can not only effectively treat industrial solid waste and construction solid waste, but also reduce the mining cost and carbon emission of new materials, further helping to realize resource recycling and green development. SUMMARY
[0005] The application aims to provide a crack-resistant full-recycled aggregate road water stable layer material and a preparation method thereof.The road water stable layer material prepared by the application makes full use of industrial solid wastes such as fly ash, slag powder, silica fume or red mud, and construction waste or road demolition waste, and the cement consumption is less, and the consumption of natural crushed stone and river sand is reduced.The production process is low in cost, green, low in carbon, energy-saving and emission-reducing, and effectively realizes the resource utilization of solid wastes.Meanwhile, the crack-resistant full-recycled aggregate road water stable layer material prepared by the application has excellent mechanical properties, durability, adhesion and bearing capacity, and the preparation method is simple in process and convenient to operate, and the adverse effects of recycled coarse and fine aggregates on the strength and volume stability are overcome, so that the actual engineering requirements are met, and the economic, social and environmental benefits are remarkable.
[0006] The application aims to provide a crack-resistant full-recycled aggregate road water stable layer material and a preparation method thereof, which can prepare the road water stable layer material by taking the recycled aggregate as the main material and apply it to the road base, and can achieve the technical indexes of the inorganic binder stable material for highway engineering and has high early strength.
[0007] The application provides a crack-resistant full-recycled aggregate road water stable layer material and a preparation method thereof.
[0008] In one of the application, a crack-resistant full-recycled aggregate road water stable layer material is provided, which comprises the following components and mass content: ordinary Portland cement 2-8 parts, industrial solid waste 0-2 parts, recycled micro powder 0-2 parts, recycled aggregate 90-94 parts, water 5-12 parts, and building additive including water reducing agent 0.3-0.7 % of the mass percentage of the main material (including ordinary Portland cement, industrial solid waste and recycled micro powder), retarder 0.05-0.2 %, hydroxypropyl methylcellulose 0.1-0.3 %, and air entraining agent 0.05-0.15 %.
[0009] The cement is P·O 425 or 325 ordinary Portland cement.The cement can greatly improve the compressive strength performance of the cementitious material, and improve the water resistance of the material.
[0010] The industrial solid waste can be one or more of fly ash, slag powder, silica fume or red mud compounded in a certain proportion, and the recycled micro powder is powder with a particle size of less than 0.075 mm in construction waste or road demolition waste.
[0011] The recycled aggregate is one or more granular materials with a particle size of 0-37.5 mm obtained by crushing construction waste, road demolition waste or tailings sandstone.
[0012] The water reducing agent is a polycarboxylic acid superplasticizer.
[0013] The retarder is a gypsum special retarder.
[0014] The viscosity of the hydroxypropyl methylcellulose is 100,000 viscosity.
[0015] The air entraining agent is sodium alkyl sulfonate.
[0016] The aggregate is crushed, ground, and sieved to be divided into different particle size groups according to different engineering requirements; the fine aggregate with a particle size of 0.075-2.36 mm is mixed at a mass ratio of 15-35%, and the coarse aggregate with a particle size of 2.36-9.5 mm is mixed at a mass ratio of 65-85%; they are respectively added to the mixer for free grading, and after sufficient stirring and uniform mixing, they can be used.
[0017] The application also provides a preparation method of the anti-cracking full-recycled aggregate road water stable layer material.
[0018] Compared with the prior art, the technical scheme of the application has the following beneficial effects.
[0019] (1) The technical scheme of the application makes full use of industrial solid wastes such as fly ash, slag powder, silica fume or red mud as test raw materials, which not only solves the problems of land resource waste and pollution caused by long-term accumulation of industrial solid wastes such as fly ash, slag powder, silica fume or red mud, but also reduces the amount of Portland cement, reduces energy consumption and environmental problems caused by cement production, and meets the requirements of energy saving, emission reduction, green and low-carbon sustainable development.
[0020] (2) The application replaces natural coarse and fine aggregates with recycled coarse and fine aggregates, which not only solves the problem of disposal of construction waste, road demolition waste or tailings sand, but also alleviates the contradiction between supply and demand of natural aggregates, and reduces the consumption of natural resources and energy.
[0021] (3) The anti-cracking full-recycled aggregate road water stable layer material prepared by the application can improve the strength, crack resistance and impermeability of the material by using industrial solid wastes such as fly ash, slag powder, silica fume or red mud, and by adding a certain proportion of admixture, the prepared water stable layer material has excellent mechanical properties, durability, adhesion, bearing capacity, and can effectively alleviate the disposal pressure of construction waste or road demolition waste, achieve the purpose of saving resources and protecting the environment, and has extremely broad application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 The figure shows the synthesis grading curve of the recycled aggregate. DETAILED DESCRIPTION
[0023] The technical scheme of the application will be described in detail below in combination with specific embodiments.
[0024] Step one: preparation of recycled aggregate.
[0025] First, the construction waste, road demolition waste or tailings sandstone is crushed, sieved according to the provisions of “Highway Engineering Aggregate Test Regulations” (JTG 3432-2024), and the excess inorganic impurities are removed, and then the artificial grading is obtained. The particle size of the aggregate is 0-31.5 mm, which meets the specification requirements.
[0026] Step two: preparation of binder (take cement fly ash as an example).
[0027] P·O 425 ordinary Portland cement and fly ash are compounded in a certain proportion.
[0028] Step three: application suitability design of a crack-resistant full recycled aggregate road water stable layer material mix ratio.
[0029] According to the crack-resistant full recycled aggregate road water stable layer material, it includes the following components and mass fraction content: ordinary Portland cement 2-8 parts, fly ash 0-4 parts, recycled aggregate 90-94 parts, water 5-12 parts, building additives including water reducing agent 0.3-0.7 % of the mass percentage of main materials (including ordinary Portland cement, fly ash), retarder 0.05-0.2 %, hydroxypropyl methyl cellulose 0.1-0.3 %, air entraining agent 0.05-0.15 %.
[0030] Step three: preparation of a crack-resistant full recycled aggregate road water stable layer material.
[0031] The calculated amount of water to be added to the test material is uniformly sprayed on the test material, and then the test material is fully mixed with a small shovel to a uniform state, and then placed in a sealed container for 4-24 h for standby. The required binder is added to the soaked test sample, and fully mixed with a small shovel, trowel or other tools to a uniform state. Referring to the test method of “Inorganic Binder Stabilized Material Compaction Test Method” (T0804-1), the test sample is subjected to heavy compaction test, and the compaction test needs to be completed within 1 h. The optimum moisture content and maximum dry density of the batch material are determined according to the method of “Highway Engineering Aggregate Test Regulations” (JTG 3432-2024).
[0032] Step four: curing of a crack-resistant full recycled aggregate road water stable layer material.
[0033] After the test piece is taken out of the test mold and weighed, it is put into a plastic film bag, the air in the bag is completely removed, the bag opening is tightly tied, and the packaged test piece is put into a curing room at 20 ± 3 ℃ and an environmental humidity of more than 95% for curing until the curing age for testing. On the last day of the curing age, the test piece is taken out and soaked in water at 20 ± 2 ℃ for 24 h. After the surface water is absorbed with a soft cloth, a unconfined compressive strength test is performed at a loading rate of 1 mm / min, and the representative value is taken from six parallel samples.
[0034] This embodiment is implemented on the premise of the technical scheme of the present application, and gives a detailed implementation mode and specific operation process, but the protection scope of the present application is not limited to the following examples.
[0035] Example 1.
[0036] A crack-resistant full-recycled aggregate road water stable layer material with a binder: aggregate ratio of 6:94 includes the following components by mass fraction: ordinary Portland cement 4 parts, fly ash 2 parts, recycled aggregate 94 parts, water reducing agent 0.45%, retarder 0.05%, cellulose 0.15%, air entraining agent 0.1%, and sample preparation and curing are performed according to the test methods and procedures.
[0037] Example 2.
[0038] A crack-resistant full-recycled aggregate road water stable layer material with a binder: aggregate ratio of 8:92 includes the following components by mass fraction: ordinary Portland cement 6 parts, fly ash 2 parts, recycled aggregate 92 parts, water reducing agent 0.35%, retarder 0.1%, cellulose 0.1%, air entraining agent 0.15%, and sample preparation and curing are performed according to the test methods and procedures.
[0039] Example 3.
[0040] A crack-resistant full-recycled aggregate road water stable layer material with a binder: aggregate ratio of 8:92 includes the following components by mass fraction: ordinary Portland cement 4 parts, fly ash 4 parts, recycled aggregate 92 parts, water reducing agent 0.35%, retarder 0.05%, cellulose 0.1%, air entraining agent 0.1%, and sample preparation and curing are performed according to the test methods and procedures.
[0041] Example 4.
[0042] A crack-resistant full-recycled aggregate road water stable layer material with a binder: aggregate ratio of 10:90 includes the following components by mass fraction: ordinary Portland cement 6 parts, fly ash 4 parts, recycled aggregate 90 parts, water reducing agent 0.3%, retarder 0.05%, cellulose 0.15%, air entraining agent 0.1%, and sample preparation and curing are performed according to the test methods and procedures.
[0043] Example 5.
[0044] A crack-resistant full-recycled aggregate road water stable layer material with a binder: aggregate = 10:90, comprising the following components by mass fraction: ordinary portland cement 8 parts, fly ash 2 parts, recycled aggregate 90 parts, water reducing agent 0.3%, retarder 0.15%, cellulose 0.15%, air entraining agent 0.15%, sample preparation and curing are carried out according to the test methods and procedures.
[0045] Comparative example.
[0046] A crack-resistant full-recycled aggregate road water stable layer material with a binder: aggregate = 6:94, comprising the following components by mass fraction: ordinary portland cement 4 parts, fly ash 2 parts, natural aggregate 94 parts, water reducing agent 0.3%, retarder 0.05%, cellulose 0.1%, air entraining agent 0.1%, sample preparation and curing are carried out according to the test methods and procedures.
[0047] The above examples 1-5 and comparative example 1 respectively prepared crack-resistant full-recycled aggregate road water stable layer materials with different proportions of binder and full-recycled aggregate, and crack-resistant full-recycled aggregate road water stable layer materials without adding recycled aggregate. The mechanical properties of the above examples are carried out according to the requirements of “Highway Engineering Inorganic Binder Stabilized Material Test Procedures” (JTG 3441-2024). The test results are shown in Table 1.
[0048] Table 1 Comparison of mechanical properties of crack-resistant full-recycled aggregate road water stable layer materials.
[0049]
[0050] As can be seen from Table 1, compared with comparative example 1, the mechanical properties of the full-recycled aggregate road water stable layer material are slightly reduced, but still meet the technical requirements of highway water stable layer, and the engineering construction performance is greatly improved. Based on the above test results, the crack-resistant full-recycled aggregate road water stable layer material proposed by the present application can meet the mechanical property requirements; the 7d unconfined compressive strength of the crack-resistant full-recycled aggregate road water stable layer material test pieces obtained by the examples and comparative examples of the present application is all above 3.5 MPa.
[0051] The above description of the examples is for the convenience of the ordinary skilled person in the art to understand and use the invention. Those skilled in the art can easily make various modifications to these examples, and apply the general principles described herein to other examples without having to go through creative labor. Therefore, the present application is not limited to the above examples, and improvements and modifications made by those skilled in the art without departing from the scope of the present application should be within the scope of protection of the present application.
Claims
1. A crack-resistant full-recycled aggregate road water stable layer material, characterized by, The raw materials include the following components in mass fraction: ordinary Portland cement 2-8 parts, industrial solid waste 0-2 parts, recycled micro powder 0-2 parts, recycled aggregate 90-94 parts, water 5-12 parts, and building admixture including water reducing agent 0.3-0.7 %, retarder 0.05-0.2 %, hydroxypropyl methylcellulose 0.1-0.3 %, and air entraining agent 0.05-0.15 % in terms of parts per million of the mass of the main materials (including ordinary Portland cement, industrial solid waste, and recycled micro powder).
2. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, characterized by, The cement is P·O 425 or 325 ordinary Portland cement. The cement can greatly improve the compressive strength performance of the cementitious material and improve the water resistance of the material.
3. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, characterized by, The industrial solid waste can be one or more of fly ash, slag powder, silica fume, or red mud compounded in a certain proportion, and the recycled micro powder is powder with a particle size of less than 0.075 mm obtained by crushing construction waste or road demolition waste.
4. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, wherein the recycled aggregate is one or more kinds of aggregate with a particle size of 0-37.5 mm obtained by crushing construction waste, road demolition waste, or tailings sandstone.
5. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, characterized in that, The water reducing agent is a polycarboxylic high-efficiency water reducing agent.
6. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, characterized by, The retarder is a gypsum special retarder.
7. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, characterized by, The viscosity of the hydroxypropyl methylcellulose is 100,000 viscosity.
8. The anti-cracking full-recycled aggregate road water stable layer material according to claim 1, characterized by, The air entraining agent is sodium alkyl sulfonate.
9. The anti-cracking full-recycled aggregate road water-stable layer material according to claim 1, wherein, The aggregate is crushed, ground, and sieved into different particle size groups, and is graded according to different engineering requirements; the fine aggregate with a particle size of 0.075-2.36 mm is added in a mass ratio of 15-35 %, and the coarse aggregate with a particle size of 2.36-9.5 mm is added in a mass ratio of 65-85 %; they are respectively added to the mixer for free grading, and are uniformly stirred for use.
10. A method of producing a crack-resistant full-recycled aggregate road water stable layer material according to any one of claims 1 to 7, characterized in that, The ordinary Portland cement, industrial solid waste, and recycled micro powder are mixed and stirred with the recycled aggregate until uniform, and are mixed and stirred with water until uniform for use.
Citation Information
Patent Citations
Anti-cracking and anti-sedimentation road water-stable layer material and preparation method thereof
CN113698164A